The effective concentration of red betel leaf (Piper crocatum) infusion as root canal irrigant solution - Fani Pangabdian; Slamet Soetanto; Ketut Suardita (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Smear layer is a debris consisting of organic and inorganic particles of calcified tissue, necrotic tissue, pulp tissue, and dentinoblast and microorganism processes that can close the entrance to the dentin tubuli. Smear layer, will not only inhibit the penetration of disinfection materials and sealers to the dentin tubuli, but will also reduce the attachment of root canal filling material so that root canal irrigation solution is needed to dissolve the smear layer. Red betel leaf (Piper crocatum) infusion, on the other hand, contains saponin characterized as “surfactants” which can dissolve smear layer. Nevertheless, the effective concentration of the red betel leaf infusion has still not been known clearly. Purpose: This study is aimed to determine the effective concentration of the red betel leaf infusion for cleaning root canal walls from smear layer. Methods: Fiveteen extracted human teeth with straight single roots were randomized into 5 groups (n=3). The specimens were then shaped by using rotary instruments up to a size of 25/.07. During instrumentation, each canal was irrigated with 10, 20, 30 and, 40% red betel leaf infusion for treatment groups, while another was irrigated with aquadest for the control group. Root canal cleanliness was observed by using scanning electron microscope (SEM). Results: There were significant differences among treatment groups (p<0.05), except in the treatment groups irrigated with red betel leaf infusion with concentrations of 30% and 40% (p>0.05). Conclusion: It can be concluded that red betel leaf infusion with a concentration of 30% is effective for cleaning the root canal walls from the smear layer.Latar belakang: Smear layer adalah suatu debris yang mengandung partikel organik dan anorganik dari jaringan terkalsifikasi, jaringan nekrotik, proses dentinoblas, jaringan pulpa dan mikroorganisme yang dapat menutup jalan masuk ke tubuli dentin. Smear layer akan menghalangi penetrasi dari bahan disinfeksi dan sealer terhadap tubuli dentin dan mengurangi perlekatan bahan pengisi saluran akar, sehingga dibutuhkan larutan irigasi yang dapat membuang smear layer tersebut. Infusa daun sirih merah (Piper crocatum) mengandung saponin yang dikarakteristikkan sebagai surfaktan yang dapat melarutkan smear layer, tetapi sampai sekarang belum ada penelitian tentang hal tersebut. Tujuan: Penelitian ini dilakukan untuk mengetahui konsentrasi efektif daya pembersih infusa daun sirih merah (Piper crocatum) dapat membersihkan dinding saluran akar dari smear layer. Metode: 15 gigi premolar bawah manusia yang mempunyai akar lurus dibagi menjadi 5 kelompok secara acak (n=3). Gigi dipreparasi menggunakan rotary instrumen sampai Protaper F2 (30/0.02). Selama instrumentasi, dilakukan irigasi dengan infusa daun sirih merah (Piper crocatum) dan konsentrasi 10, 20, 30, 40% dan diirigasi aquadest untuk grup kontrol. Setelah itu kebersihan dinding saluran akar diperiksa dengan menggunakan scanning electron microscope (SEM). Hasil: Terdapat perbedaan yang signifikanantara masing-masing kelompok (p<0,05), kecuali kelompok yang diirigasi infusa daun sirih merah (Piper crocatum) konsentrasi 30% dan 40% (p>0,05). Kesimpulan: Dapat disimpulkan infusa daun sirih merah (Piper crocatum) dengan konsentrasi 30% efektif untuk membersihkan dinding saluran akar dari smear layer.